Retrospective Analysis of Levetiracetam Compared to Phenytoin for Seizure Prophylaxis in Adults with Traumatic Brain Injury. Issue 9 (September 2013) - Caballero, G. Christina; Hughes, Darrel W.; Maxwell, Pamela R.; Green, Kay; Gamboa, Conrado D.; Barthol, Colleen A.
Background: Phenytoin is standard of care for seizure prophylaxis following traumatic brain injury (TBI). Levetiracetam, an alternative antiepileptic drug, is utilized for seizure prophylaxis despite limited data supporting its use. Objective: Our primary outcome was post-TBI seizure activity measured by electroencephalogram (EEG) for levetiracetam versus phenytoin. Secondary outcomes were length of intensive care unit (ICU) stay, requirement for additional antiepileptic drugs (AED), and drug and monitoring costs. Methods: A retrospective review was performed of patients admitted to neurosurgical or surgical trauma ICU. Adult patients with at least 1 day of EEG monitoring were included. Patients were excluded if they had history of epilepsy, prior TBI, less than 48 hours of AED therapy, or additional AED prior to EEG monitoring. Results: A total 90 patients met inclusion criteria, with 18 receiving levetiracetam and 72 receiving phenytoin. Prevalence of EEG-confirmed seizure activity was similar between the levetiracetam and phenytoin groups (28% vs 29%; P = .99). ICU length of stay (13 vs 18 days; P = .28), time to EEG-confirmed seizure activity (4 vs 6 days; P = .24), and duration of seizure prophylaxis (9 vs 14 days; P = .18) were also similar. The median daily cost of levetiracetam therapy was $43 compared to $55 for phenytoin therapy and monitoring ( P = .08). When all anticonvulsant therapy and monitoring were included, costs were lower for the levetiracetam group ($45 vs $83; P = .02). Conclusion: Levetiracetam may provide an alternative treatment option for seizure prevention in TBI patients in the ICU. Total antiepileptic drug and monitoring costs were lower for levetiracetam patients.